Suitability of black currant (Ribes nigrum L.) as bred by NULES of Ukraine to machine harvesting of its berries - В. О. Сіленко; П. М. Гав’юк (Plant Varieties Studying and Protection)
In the article the authors show outcome of three years observation of blackcurrant varieties bred by Study Horticulture Department NULES of Ukraine for their suitabi lity to machine harvesting. Blackcurrant is the most common berry crop in Ukraine. When establishing intensive industrial plantations the varieties suitable for machine harvesting should be used. During 2006-2008 limited and unlimited traits of varieties bred by NULES of Ukraine suitability to combine harvesting were studied. All parameters of the examined varieties were compared against the requirements of the «ideal variety”. Simultaneous ripening of berries was observed in varieties Dochka Vorskly – 93,6%, Hovtva, Pamyaty Leonida Myhalevskoho – 92,6%. The pick off effort required to collect berries out of their clusters for all varieties but Yarynka was within acceptable range of 67...129 g. By effort applied for berries crush only Yarynka has failed to meet the necessary requirements. All the varie ties but Yarynka have been found suitable by growth habit of their bush (upright and semi-spread). Insufficient number fruits (6-7 pc.) in clusters for varieties Narodna and Yarynka was noted. Berries weight for all studied varieties ranged within 1.27-1.84 g, their drop-off was 3-8%, duration of harvesting period ranged from 8 to 10 days, so all the parameters of varieties suggested they were suitable for picking berries by berry harvesters. Varieties Dochka Vorskly, Universitetska, Hovtva, Pamyatna, Premiera, Narodna, Leleka and Pamyaty Leonida Myhalevskoho were selected as suitable for combine harvesting by the complex of positive parameters.